Bridging Economics and English: A Comprehensive Review of ESP Instruction for EFL Students - Himaya Praptani Adys (Journal of Innovative and Creativity, 2025)
The integration of English for Specific Purposes (ESP) in the field of economics within the EFL (English as a Foreign Language) context has become increasingly crucial in preparing students to navigate the global economic landscape. This narrative literature review examines recent developments in economic English instruction for EFL students during the period 2019-2024. Through systematic analysis of relevant publications, this study identifies key methodological trends, technological innovations, persistent challenges, and effective solutions in economic ESP instruction. The findings reveal a significant shift toward task-based learning approaches, increased integration of digital technology, and emphasis on authentic materials. Primary challenges include specialized vocabulary acquisition, academic writing skills, and confidence in professional communication. This review concludes with recommendations for educators and researchers in developing more effective economic ESP curricula.